Application of automated trajectory design for pilot flight assessment during route flights. Issue 3 (3rd July 2017) - Masiulionis, Tadas; Miniotas, Darius; Rudinskas, Darius; Kikutis, Ramūnas; Masiulionienė, Gabrielė
Abstract: Flight accuracy in the airspace is becoming an increasingly difficult issue due to the expanding number of aircraft operating in it. In order to meet the needs of all airspace users, aircraft flows are being increased, and different aircraft systems that minimise the risk of aircraft accidents are being developed to ensure flight safety. However, statistically, the impact of the human factor on aviation accidents and incidents remains high. This article focuses on the assessment of pilot flight accuracy during route flights and presents a methodology based on automated assessment tunnels for accurately assessing pilot flight deviations from a pre-set flight trajectory axis both on the horizontal and vertical plane.